Records in context: The road of archives to semantic interoperability - Pastor-Sánchez, Juan-Antonio; Llanes-Padrón, Dunia (Anuario ThinkEPI, 2017)
In recent years there have been changes to the theoretical and methodological approaches to archival descriptions. Technologies and new users have forced change to the methods of conceiving the description process. The postmodern paradigm has influenced the way in which information is represented, blurring the borders between archives, libraries, and museums. In this context, the International Council of Archives has developed a conceptual model for the description called Records in context. This model unifies the ISAD(G), ISAAR(CPF), ISDF, and ISDIAH standards and establishes the entities, properties, and relationships of the archival descriptions. The model facilitates decentralized semantic interoperability and enables the development of an OWL ontology for the representation and publication of archival datasets using semantic web technologies. Records in context places archival resources within the dynamics of direct Web publishing and offer